First Record of Marine Dinoflagellate, Alexandrium Tamutum (Dinophyceae) from Malaysia - Kon, Nyuk Fong; Hii, Kieng Soon; Tan, Toh Hii; Yek, Leh Hie; Lim, Po Teen; Leaw, Chui Pin (Malaysian Abstracting and Indexing System, 2013)
Several species of dinoflagellates in the genus Alexandrium are known to be toxic, and have been associated with paralytic shellfish poisoning (PSP) in Malaysia. These Alexandrium species showed high morphological similarity among the toxic and non-toxic species, and detailed observation of the thecal plate’s arrangement is required for precise species identification. Co-occurrence of the toxic and non-toxic species has complicated the plankton monitoring of PSP. In this study, a clone of Alexandrium species was established from plankton samples collected from Kota Belud, Sabah. The specimen was observed under epi-fluorescence microscope, and nucleotide sequences of the nuclear-encoded ribosomal RNA gene obtained. Morphologically, the clone showed relatively wide and large sixth precingular plate (6´´) compared to that of A. minutum. The sulcal posterior plate (Sp) is similar to that of A. minutum, which is wider than long. The first apical plate (1´) is irregularly rhomboidal with a small ventral pore (vp) present on its right margin. The morphological characters resembled to the species description of A. tamutum. Phylogenetic analysis of the ITS rDNA region also revealed a monophyly of this clone with other strains of A. tamutum, and separating them from the A. minutum clade. Species-specific sequence signatures of A. tamutum were obtained in silico, which could be as potential oligonucleotide probe regions for species detection by using molecular tool. This represents the first report of A. tamutum found in Malaysian waters.